Five Essential Principles for First Web Space Reconstruction in the Burned Hand. Issue 5 (November 2020) - Greyson, Mark A.; Wilkens, Suzanne C.; Sood, Ravi F.; Winograd, Jonathan M.; Eberlin, Kyle R.; Donelan, Matthias B.
Abstract : Background: Burn injuries commonly affect the hand, and the development of adduction contractures of the first web space is frequent and deleterious, both functionally and aesthetically. Many corrective techniques and algorithmic approaches have been described to treat this problem, but there is no consensus on the optimal management. Methods: A retrospective review at a single high-volume pediatric burn center was undertaken to evaluate the clinical course of these patients. All pediatric patients undergoing initial release of burn scar contracture of the first web space from 2005 through 2015 were included in a retrospective cohort study. Results: The authors identified 40 patients with 57 burned hands. The initial approach to management was variable. Z-plasty or other local flap was the first technique used in 28 hands (49 percent), split-thickness skin graft in 19 hands (33 percent), full-thickness skin graft in seven hands (12 percent), groin flaps in two hands (4 percent), and a reverse radial forearm flap in one hand (2 percent). The mean numbers of total reconstructive procedures per hand including the initial procedure were as follows: groin flap, 4.0; full-thickness skin graft, 3.1; split-thickness skin graft, 2.1; Z-plasty, 1.4; and reverse radial forearm flap, 1.0. Conclusions: Successful reconstruction of the first web space must be addressed in the context of the entire hand. It is the authors' preference to use split-thickness skin grafting whenever a skin deficiency is present—only then should leading edge contractures be addressed with Z-plasty. Based on their experience, the authors recommend five principles that are essential to successfully treat postburn contractures of the first web space. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.